Association between Corneal Stiffness Parameter at the First Applanation and Keratoconus Severity - Kaili Yang; Liyan Xu; Qi Fan; Shengwei Ren (Journal of Ophthalmology)
Objective. The study aimed to evaluate the character of corneal stiffness parameter at the first applanation (SP-A1) in normal and keratoconus eyes and explore the association between SP-A1 and keratoconus severity indicators. Methods. A total of 351 normal and 351 keratoconus eyes were included in the current study. Keratoconus was diagnosed according to the corneal topography map and slit-lamp examination. The severity of keratoconus was classified to mild (steep keratometry (Ks) < 48D), moderate (48 ≤ Ks < 55D), and severe (Ks ≥ 55D). The SP-A1 was measured using the Corvis ST software. The correlation analyses and receiver operating characteristic (ROC) curve were performed in the current analysis. ResultsThe SP-A1 values of keratoconus were lower than that of normal eyes (72.11 (57.02, 83.08) mmHg/mm vs 110.89 (100.45, 122.47) mmHg/mm, P<0.001). With the severity of keratoconus increasing, the SP-A1 decreased and the value of SP-A1 was 79.54 (70.30, 90.93) mmHg/mm, 65.11 (53.14, 77.46) mmHg/mm, and 47.59 (37.50, 62.14) mmHg/mm in mild, moderate, and severe keratoconus eyes, respectively (P<0.001). The negative association between SP-A1 and Ks was found in mild, moderate, and severe keratoconus eyes (r mild = -0.171, rmoderate = -0.317, rsevere = −0.288, all P<0.05). A positive association between SP-A1 and the thinnest corneal thickness (TCT) was found in all eyes (rnormal = 0.687, rmild = 0.519, rmoderate = 0.488, rsevere = 0.382, all P<0.05). SP-A1 was found to be statistically positively associated with intraocular pressure (IOP), biomechanical corrected IOP (bIOP), time from the initiation of air puff until the first applanation (A1T), corneal velocity at the second applanation (A2V), and negatively associated with deformation amplitude (DA), peak distance (PD), corneal velocity at the first applanation (A1V), time from the initiation of air puff until the second applanation (A2T), and DA Ratio Max [2 mm] both in normal and keratoconus eyes (all P<0.05). The ROC analysis indicated that the AUC (95% CI) of SP-A1 was 0.952 (0.934–0.967) and 0.930 (0.904–0.951) in detecting keratoconus eyes and mild keratoconus eyes from normal eyes, respectively. Conclusions. The SP-A1 value decreased while the keratoconus severity increased. It was lower in keratoconus than that in normal eyes and could be helpful in identifying keratoconus eyes from normal eyes. Further researches would be warranted to expand the clinical utility of SP-A1.